Alcohol and physical activity screening in the National Health Service Health Check programme: Comparison of medical records and actual practice - Victoria Riley; Christopher Gidlow (Elsevier, 2022)
Objectives: National data for the National Health Service (NHS) Health Check programme (in England), collected by University College London, Public Health England and NHS Digital, found that physical activity and alcohol was recorded in just 64.5% and 38.3% of patient records, respectively. We examined video recorded NHS Health Checks from the RIsk COmmunication in NHS Health Check study (collected 2018-19) to explore alcohol and physical activity measurement, comparing recorded and actual activity. Study design: Observational study. Methods: Anonymised medical records and transcripts of 130 video-recorded NHS Health Checks from 12 general practices were compared to understand use of alcohol (Alcohol Use Disorders Identification Test, Alcohol Use Disorders Identification Test-Concise, Fast Alcohol Screening Test) and physical activity (General Practitioner Physical Activity Questionnaire) measures. Results: Findings showed considerable discrepancies between how alcohol measurement was recorded in the patient's medical record and how it was assessed in practice. Equally, practitioners completed or partially completed AUDIT in fewer than half of patients who were perceived to be eligible for further screening. There was more consistency in physical activity assessment. Omitted questions, related to physical activity, were largely around work-related physical activity. Conclusions: Overall, inconsistent use of recommended tools for screening alcohol and physical activity in NHS Health Check suggests that some practitioners do not follow recommended national guidance. Omission of certain questions led to missed opportunities for practitioners to discuss alcohol consumption, particularly with those who reported apparently excessive alcohol consumption (>14 units per week). Interviews with NHS Health Check practitioners may help to understand barriers to following recommended practice and identify areas for improvement. Classification: Restricted.